Grave’s disease in 32-34 weeks of pregnancy - Jimmy Toga Sitorus; Cut Meurah Yeni (Syiah Kuala University, 2011)
The objective of the present case report was to improve knowledge in the management of pregnancy and delivery with Graves’ disease in 32-34 weeks of pregnancy. Primigravida with Graves’ disease was detected at 28 weeks gestational age in patients Mrs. H, 26 years old came with complaints : shortness of breath, leg sweeling, a lump in the neck, the eyes stood out, finger tremors, can not stand the heat, often sweaty, the hearts was tachycardia, increased appetite but weight doesn’t increase and even decreased 8 kg since last five years ago. Patients had a history of goitre since five years ago, with an irregular treatment. Pregnancy can be maintained after being treated in Departement of Obstetrics and Gynaecology and routinely controlled to assess fetal wellbeing. At 32-34 weeks of gestational age, the pregnancy was terminated by caesarean section, born baby boy, 1930 gr, Apgar Score 8/9. Mother was in good condition after caesarean section. Baby was dead in six days after birth with respiratory distress syndrome DD/ pneumonia aspiration. Hyperthyroidism which not handled will have a serious complications, but if properly handled and monitored, maybe the results of maternal and fetal outcomes expected good. Antepartum fetal assessment include fetal heart rate, the amount of amniotic fluid can be a parameter for pregnancy termination planning. The results of poor outcomes are things that must be observed that Graves’ disease in pregnancy have a risk of neonatal mortality